(untitled) (UNED Research Journal, 2019)
Introduction: early musical stimulation is a useful tool that improves development in linguistics, and in motor, cognitive and social skills in small children. The process is complex and specific and can be done by ear or by writing a score. Objective: to develop a method with children’s songs to stimulate from babies to children of three years that can be used from individuals to public and private institutions such as care networks and day care centers. Methods: based on my own family experience, I recommend five stages: preliminary (listening to classical music inside the womb), stage one (music that shows love for the children), stage two (music to develop gross motor skills), stage three (music for fun and social skills) and stage four (music to develop cognitive skills). Result: music as an early stimulation tool reinforces the love bond between parents and child and could promote the bond between teachers and children. Conclusion: my impression is that the method had positive effects on my children’s sleep, gross motor skills, social adeptness, cognitive development and linguistics.